Pendapatan Usahatani Kelapa Di Desa Makasili Kecamatan Kumelembuai Kabupaten Minahasa Selatan - Winokan, Niklin; Tarore, Melissa Lady Gisela; Rumagit, Grace Adonia Josefina (AGRI-SOSIOEKONOMI, 2023)
The study aims to determine and analyze the amount of coconut farming income in Makasili Village, Kumelembuai District, South Minahasa Regency. This research was conducted from January to March 2023. The research was conducted in Makasili Village, Kumelembuai District, South Minahasa Regency. Sampling was done intentionally (porposive sampling), which became the sample in this study as many as 18 people. The data analysis method that will be used in this study is to use quantitative analysis, namely analyzing, describing and summarizing various situational conditions from various data collected. The results showed that the average income of coconut farmers was IDR 6,426,844 for each harvest season from the average sale of 1,025 kg of copra at a price of IDR 6,000 to IDR 8,000 for each kilogram with a 10% to 12% discount. The total income earned by coconut farmers in Makasili Village, Kumelembuai District, South Minahasa Regency amounted to IDR 84,681,233. The average income of farmers obtained from coconut farming for one harvest season is IDR 4,704,513. The income generated from copra production for each hectare of farmer's land area is IDR 3,650,053/Ha and for each tree is IDR 41,368/tree.